THE USE OF QUIZ-DEMONSTRATION-PRACTICE-REVISION (QDPR) TO IMPROVE STUDENTS’ PRONUNCIATION - Sujariati, Sujariati; Larasati, Titin (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The objective of this research was to find out whether or not the use of Quiz-Demonstration-Practice-Revision (QDPR) learning model can improve students’ pronunciation especially in pronouncing sound /f/, /v/, /θ/, and /t/. The method of this research was pre-experimental with one group pre-test and post-test as an instrument of the research. The population of the research was the eleventh grade of SMA Negeri 11 Pangkep that consisted of 240 students. The number of samples was 30 students. The data collection consisted of pre-test, treatment and post-test. Forms of pre-test and post-test were oral test that contained 20 words that related with the focus sounds. The findings of the research showed that the students’ mean score of pre-test before treatment was (39.17). While after treatment, the mean score of post-test was (76.83). Therefore, the significant between pre-test and post-test was 96%. In order that, the researcher assumed that using Quiz-Demonstration-Practice-Revision (QDPR) could improve students’ pronunciation correctly especially in pronouncing sound /f/, /v/, and /θ/, /t/. Thus, QDPR can be an alternative model to English pronunciation instruction in English classrooms